2019
DOI: 10.1007/s13318-019-00541-3
|View full text |Cite
|
Sign up to set email alerts
|

In-Vivo Degradation of DNA-Based Therapeutic BC 007 in Humans

Abstract: Background and Objectives Since there is no clear evidence in the literature to show how non-modified single-stranded DNA (ssDNA) drugs are metabolized in humans, we assessed the metabolism of BC 007, an ssDNA therapeutic, under development as a neutralizer of autoantibodies against G-protein-coupled receptors. In-vitro, investigating its stability in monkey plasma and serum, a successive 3′-exonuclease degradation resulting in several n – x de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…In all subjects of Cohorts 4 and 5 (1350 and 1900 mg), an increase in uric acid was seen, beginning 50 min after the start of the infusion, with peak values at 120 and 110 min after the start of the infusion, respectively, with only slight elevation left on Day 2 and complete return to baseline on Day 8. This increase was within the normal physiologic range [23].…”
Section: Bc 007 Safetysupporting
confidence: 59%
See 1 more Smart Citation
“…In all subjects of Cohorts 4 and 5 (1350 and 1900 mg), an increase in uric acid was seen, beginning 50 min after the start of the infusion, with peak values at 120 and 110 min after the start of the infusion, respectively, with only slight elevation left on Day 2 and complete return to baseline on Day 8. This increase was within the normal physiologic range [23].…”
Section: Bc 007 Safetysupporting
confidence: 59%
“…With respect to metabolism, the proportion of 7% of 3′-exonuclease cleaved compound is low, especially since Shaw et al published an effective 3′-exonuclease decay in monkey plasma and serum in 1995 [21]. It was, therefore, also already looked for further down breakdown products, identifying the increase of nucleobase decay products immediately after the start of the infusion, which was described in detail by Davideit et al [23]. This fast and full degradation down to nucleic base degradation products in humans was an astonishing fact and one of the first reports about the fate of DNA-drugs in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Kittel et al. ( 86 ) detected three-fold higher plasma BAIBA concentrations in a small number of subjects with AGXT2 gene deficit; however, none of the studies reported any adverse effect of increased endogenous BAIBA, suggesting that endogenous and exogenous factors resulting in high plasma BAIBA levels do not have any pathological effect ( 87 ). Notably, in pathological situations with substantial DNA degradation, such as malignancy ( 84 , 88 ), radiation ( 89 ), and short-term starvation ( 90 ), the levels of BAIBA in urine are elevated.…”
Section: Prospects Of Baiba Being Used As An Exercise Pill?mentioning
confidence: 99%
“…Although BAIBA can be detected in both blood and urine, the time course in the two matrices may not be the same. After an intervention with the DNA-based drug BC007, plasma BAIBA concentrations were found to increase after 3 min, reached a maximum after 60 min, and declined to baseline levels ( 87 ). The same intervention led to a rise in urinary BAIBA levels within a maximum of 2−4 h and a decline to pre-intervention levels over 8–12 h. BAIBA was considered to be metabolized rapidly in plasma, with urine representing a better matrix for testing, since sampling is non-invasive and the time profile is more favorable for testing.…”
Section: Applicability Of Baiba As a Useful Biomarker?mentioning
confidence: 99%
“…The 2 products may be useful in tracking the metabolism of the drug. 81 According to the sponsor, BC007 is currently under investigation for persistence of β 1 -AR autoantibody removal in autoantibody-positive HF patients in phase IIa of clinical testing.…”
Section: Safety and Tolerability Of Aptamer Treatmentmentioning
confidence: 99%